Proving and implementing the effectiveness of iDnc for optimal 4D data signature-based cluster models of NLEX Traffic Density Data Sets - Maravilla, Jr., Reynaldo G.; Tabanda, Elise Raina A.; Tadlas, Rona May U.; Malinao, Jasmine A.; Adorna, Henry N. (Philippine computing journal)
This paper used the improved cluster validity index, known as iDnc, of an existing cluster validity index Dnc. It is implemented to determine which data signature construction generates the optimal cluster models for periodic time series density data set. Furthermore, we proved the effectiveness of iDnc to show that the said cluster validity index is indeed improved from Dnc. Among the candidate data signatures identified in previous literature, the 4D data signature was found to be the most effective in generating the optimal cluster models for traffic density data set based on iDnc computations. We showed the robustness of the 4D data signature construction by implementing these computations and the Kruskal-Wallis Test on multiple segments of the North Luzon Expressway (NLEX). With the resulting optimal cluster model for density, traffic analysis using the data signature visualization technique data image was done on 4 different NLEX segments.